(untitled) (International Journal of Engineering and Computer Science, 2015)
One fascinating thing about artificial neural networks is that, they are mainly inspired by the human brain. This doesn’t mean that Artificial Neural Networks are exact simulations of the biological neural networks inside our brain - because the actual working of human brain is still a mystery. The concept of artificial neural networks emerged in its present form our very limited understanding about our own brain ("I know that I know nothing").